Kandungan Senyawa Oleoserin Baeckea. frutescens L Pada Beberapa Pelarut: Compound Content in Baeckea oleoserin. frutescens L On Some Solvents - Jemi, Renhart; Nuwa, Nuwa; Sitorus, Lamboris Rianto (HUTAN TROPIKA, 2023)
The aim of the research is to analyze the compounds contained in Baeckea oleoresin. frutescens L which is soluble in n-hexane, chloroform and ethyl acetate. B. frutescens L oleoresin resulting from multilevel fractionation with n-hexane, chloroform and ethyl acetate solvents was analyzed using GCMS (Gas Chromatography-Mass Spectrometry). Then analyze the content. As a result, the solvent was able to dissolve many oleoresis compounds, namely n-hexane dissolving 7-Hydroxy-7-phenyl-3,9-diisopropyl-2,10-dic, chloroform solution; chloroform solvent dissolves Acetic acid ethyl ester; while ethyl acetate dissolves 1-Heptan-1,1-D2-OL. all three solvents were able to dissolve 1,8-Cineol. The conclusion is that oleoresin resulting from multilevel fractionation is able to dissolve aromatic group compounds, carboxylic acids, seikuiterpenes and monoterpenes. KEY WORD : oloeresin, Baeckea. frutescens L, fractionation, GCMS, 1,8-cineol,